Aminoferrocene-Based Anticancer Prodrugs Labelled with Cyanine Dyes for in vivo Imaging - Özkan, Hülya; Toms, Johannes; Maschauer, Simone; Prante, Olaf; Mokhir, Andriy (European Journal of Inorganic Chemistry, 2021)
N-alkylaminoferrocene-based (NAAF) prodrugs are activated in the presence of reactive oxygen species (ROS), based on which these prodrugs target cancer cells (high ROS) and do not affect normal cells (low ROS). To gain some insights into their mode of action in vivo, we have investigated the biodistribution of 18F-labelled NAAF prodrugs in tumor-bearing mice by positron emission tomography (PET). Due to the short half-life of 18F, the experimental time frame was restricted to 60 min. To extend the observation window, a more stable marker is required. In this paper, we report on conjugates of NAAF prodrugs with two cyanine dyes Cy5 and Cy7 including details of their synthesis, characterization and basic properties in cell free settings and their cellular uptake in representative human cancer cells. Finally, the Cy5 conjugate was subjected to in vivo fluorescence imaging studies to determine the prodrug biodistribution over 24 h.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Anticancer; Ferrocene; Imaging; Prodrug; Reactive oxygen species

Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Agarwal, Rahul; Götz, Theresa Ida; Soare, Alina; Cordes, Michael; Prante, Olaf; Prante, Olaf; Bergmann, Christina; Kleyer, Arnd; Ritt, Philipp; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG 4 -related disease. Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG 4 -related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68 Ga-FAP inhibitor (FAPI)-04), 18 F-fluorodeoxyglucose (FDG), MRI and histopathological assessment. In a longitudinal approach, 18 F-FDG and 68 Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Results Using combination of 68 Ga-FAPI-04 and 18 F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG 4 -related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18 F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG 4 + cells in histology, while 68 Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Conclusion FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG 4 -related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG 4 -related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team Scopus Importer:2020-10-30
Keywords: fibroblasts; health care; inflammation; outcome assessment

Evaluation of N-alkylaminoferrocenes for in-vivo imaging of reactive oxygen species activity using PET and optical imaging - Toms, Johannes; Maschauer, Simone; Daum, Steffen; Reshetnikov, Viktor; Mokhir, Andriy; Prante, Olaf (JOURNAL OF LABELLED COMPOUNDS & RADIOPHARMACEUTICALS, 2019)
CRIS-Team WoS Importer:2019-06-18

Identification of Boronic Acid Derivatives as an Active Form of N-Alkylaminoferrocene-Based Anticancer Prodrugs and Their Radiolabeling with 18F - Daum, Steffen; Toms, Johannes; Reshetnikov, Viktor; Özkan, Hülya; Hampel, Frank; Maschauer, Simone; Hakimioun, Amir Hossein; Beierlein, Frank; Sellner, Leopold; Schmitt, Michael; Prante, Olaf; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
N-Alkylaminoferrocene (NAAF)-based prodrugs are activated in the presence of elevated amounts of reactive oxygen species (ROS), which corresponds to cancer specific conditions, with formation of NAAF and p-quinone methide. Both products act synergistically by increasing oxidative stress in cancer cells that causes their death. Though it has already been demonstrated that the best prodrugs of this type retain their antitumor activity in vivo, the effects were found to be substantially weaker than those observed in cell cultures. Moreover, the mechanistic studies of these compounds in vivo are missing. For clarification of these important questions, labeling of the prodrugs with radioactive moieties would be necessary. In this paper, we first observed that the representative NAAF-based prodrugs are hydrolyzed in dilute aqueous solutions to the corresponding arylboronic acids. We confirmed that these products are responsible for ROS amplification and anticancer properties of the parent prodrugs. Next, we developed the efficient synthetic protocol for radiolabeling the hydrolyzed NAAF-based prodrugs by [18F]fluoroglucosylation under the conditions of the copper(I)-catalyzed azide–alkyne 1,3-dipolar cycloaddition and used this protocol to prepare one representative hydrolyzed NAAF-based prodrug radiolabeled with 18F. Finally, we studied the stability of the 18F-labeled compound in human serum in vitro and in rat blood in vivo and obtained preliminary data on its biodistribution in vivo in mice carrying pancreatic (AR42J) and prostate (PC3) tumors by applying PET imaging studies. The compound described in this paper will help to understand in vivo effects (e.g., pharmacokinetics, accumulation in organs, the nature of side effects) of these prodrugs that will strongly contribute to their advancement to clinical trial

Radiosynthesis of an 18 F-fluoroglycosylated aminoferrocene for in-vivo imaging of reactive oxygen species activity by PET - Toms, Johannes; Reshetnikov, Viktor; Maschauer, Simone; Mokhir, Andriy; Prante, Olaf (Journal of Labelled Compounds & Radiopharmaceuticals, 2018)
The imaging of reactive oxygen species (ROS) at the molecular level with high sensitivity and specificity by positron emission tomography (PET) could be of enormous interest to increase our knowledge about ROS activity and signalling, especially in tumours. The aim of this research was to optimise the click chemistry-based radiosynthesis of an 18 F-labelled aminoferrocene glycoconjugate that was derived from an N-alkylaminoferrocene lead structure known to have anticancer activity in vitro. Applying the solvent system phosphate buffer/THF (12/5), Cu(OAc)2 and sodium ascorbate as reducing agent at 60°C, the alkyne 1 reacted with the 18 F-labelled glycosyl azide [18 F]2 in the presence of carrier 3 (47μM) to obtain carrier-added [18 F]4 in a radiochemical yield of 85%. Interestingly, the addition of carrier was essential for sufficient radiochemical yield, because it suppressed the oxidation of no-carrier-added (n.c.a.) [18 F]4. Future work will include the formulation of c.a. [18 F]4 for studying its biodistribution in tumour-bearing mice.
EVALuna2:212380

Targeting Fibroblast Activation Protein: Radiosynthesis and Preclinical Evaluation of an 18F-Labeled FAP Inhibitor - Toms, Johannes; Kogler, Jürgen; Maschauer, Simone; Daniel, Christoph; Schmidkonz, Christian; Kuwert, Torsten; Prante, Olaf (Journal of Nuclear Medicine, 2020)
Fibroblast activation protein (FAP) has emerged as an interesting molecular target used in the imaging and therapy of various types of cancers. 68Ga-labeled chelator-linked FAP inhibitors (FAPIs) have been successfully applied to PET imaging of various tumor types. To broaden the spectrum of applicable PET tracers for extended imaging studies of FAP-dependent diseases, we herein report the radiosynthesis and preclinical evaluation of an 18F-labeled glycosylated FAPI ([18F]FGlc-FAPI). Methods: An alkyne-bearing precursor was synthesized and subjected to click chemistry-based radiosynthesis of [18F]FGlc-FAPI by 2-step 18F-fluoroglycosylation. FAP-expressing HT1080hFAP cells were used to study competitive binding to FAP, cellular uptake, internalization, and efflux of [18F]FGlc-FAPI in vitro. Biodistribution studies and in vivo small-animal PET studies of [18F]FGlc-FAPI compared with [68Ga]Ga-FAPI-04 were conducted in nude mice bearing HT1080hFAP tumors or U87MG xenografts. Results: [18F]FGlc-FAPI was synthesized with a 15% radioactivity yield and a high radiochemical purity of more than 99%. In HT1080hFAP cells, [18F]FGlc-FAPI showed specific uptake, a high internalized fraction, and low cellular efflux. Compared with FAPI-04 (half maximal inhibitory concentration [IC50] = 32 nM), the glycoconjugate, FGlc-FAPI (IC50 = 167 nM), showed slightly lower affinity for FAP in vitro, whereas plasma protein binding was higher for [18F]FGlc-FAPI. Biodistribution studies revealed significant hepatobiliary excretion of [18F]FGlc-FAPI; however, small-animal PET studies in HT1080hFAP xenografts showed higher specific tumor uptake of [18F]FGlc-FAPI (4.5 percentage injected dose per gram of tissue [%ID/g]) than of [68Ga]Ga-FAPI-04 (2 %ID/g). In U87MG tumor-bearing mice, both tracers showed similar tumor uptake, but [18F]FGlc-FAPI showed a higher tumor retention. Interestingly, [18F]FGlc-FAPI demonstrated high specific uptake in bone structures and joints. Conclusion: [18F]FGlc-FAPI is an interesting candidate for translation to the clinic, taking advantage of the longer half-life and physical imaging properties of 18F. The availability of [18F]FGlc-FAPI may allow extended PET studies of FAP-related diseases, such as cancer, but also arthritis, heart diseases, or pulmonary fibrosis.
CRIS-Team Scopus Importer:2020-12-11
Keywords: 18F; 18F-fluoroglycosylation; cancer-associated fibroblasts; fibroblast activation protein; PET